ANALISIS KUALITAS PELAYANAN PUBLIK DALAM PENGURUSAN PENDAFTARAN NIKAH DI KANTOR URUSAN AGAMA (KUA) - Ummi Khairun Nisa; Februati Trimurni (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the quality of public services in the administration of marriage registration at the Office of Religious Affairs (KUA). Marriage administrative services represent a form of public service that directly interacts with the community and serves as an important indicator in assessing the performance of government institutions. Common issues in marriage registration services include limited facilities and infrastructure, insufficient human resources, and a lack of public understanding regarding administrative procedures. This research employs a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the quality of marriage registration services at the KUA has generally been implemented quite well based on the indicators of tangibles, reliability, responsiveness, assurance, and empathy. However, improvements are still needed in service facilities, service efficiency, and the optimization of information technology utilization to enhance public satisfaction.